1968
DOI: 10.1042/bj1090757
|View full text |Cite
|
Sign up to set email alerts
|

The action of paraquat and diquat on the respiration of liver cell fractions

Abstract: 1. Paraquat and diquat produce only a slight increase in the oxygen uptake of rat liver mitochondria, and it is likely that they do not penetrate the mitochondrial membrane. 2. In mitochondrial fragments inhibited by antimycin A or by Amytal, both substances stimulate oxygen uptake with NADH or beta-hydroxybutyrate as substrate but not with succinate. The NADH dehydrogenase of the respiratory chain appears to be involved, at a site only partially inhibited by Amytal. 3. An NADPH oxidase activity is stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(50 citation statements)
references
References 8 publications
5
44
1
Order By: Relevance
“…This activity was not inhibited by cyanide or antimycin A, indicating that the actions of paraquat were not dependent on mitochondrial respiration. These data are consistent with redox cycling of paraquat (14,17). Increases in oxygen utilization by paraquat in lung epithelial cells were inhibited by DPI, indicating that redox cycling occurs via an FAD-dependent enzyme.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This activity was not inhibited by cyanide or antimycin A, indicating that the actions of paraquat were not dependent on mitochondrial respiration. These data are consistent with redox cycling of paraquat (14,17). Increases in oxygen utilization by paraquat in lung epithelial cells were inhibited by DPI, indicating that redox cycling occurs via an FAD-dependent enzyme.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have suggested that paraquat-induced redox cycling occurs via cytochrome P450 reductase (3,14,62). In contrast, our findings demonstrate that cells overexpressing this enzyme do not display increased oxygen uptake when compared with non-overexpressing parental cells, indicating that cytochrome P450 reductase is not a major contributor to paraquat-induced changes in cellular oxygen flux.…”
Section: Discussioncontrasting
confidence: 55%
“…In 1968, Gage (24) reported that anaerobic incubation of liver microsomes with NADPH (25)(26)(27) and lung (25,28,29) microsomal hydrogen peroxide production, as measured by the conversion of methanol to formaldehyde. These observations again suggested the potential for a two-electron reduction of molecular oxygen catalyzed by paraquat.…”
Section: Mechanisms Of Paraquattoxicity Redox Cycling Of Paraquatmentioning
confidence: 99%
“…Paraquat, a well-known herbicide, causes severe injury to the lungs and other organs mediated by toxic reactive oxygen species [5,6] as well as lipid peroxidation that may result in cell death. [7,8] ROS as a natural byproduct of the normal metabolisms of oxygen may play important roles in cell signaling.…”
Section: Discussionmentioning
confidence: 99%